(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the issues of preparing students for professional activity through interdisciplinary education in the professional education system are covered. Methodological, technological, pedagogical, psychological and philosophical aspects of ensuring coherence, principles of interdisciplinary integration in the educational process, substantive and organizational aspects of creating integrative science programs for the professional education system are also described.